2013
DOI: 10.1088/0957-4484/24/15/155502
|View full text |Cite
|
Sign up to set email alerts
|

Short and long range surface plasmon polariton waveguides for xylene sensing

Abstract: Nanostructured plasmonic sensors are fabricated as sinusoidal surface plasmon metallic gratings (SPGs) embedded in a functional and porous hybrid sol-gel material, phenyl-bridged polysilsesquioxane (ph-PSQ). The metal layer is in contact with the environment through the sol-gel film, which works as sensitive element, changing its dielectric properties upon interaction with aromatic hydrocarbons. The combination of sensitivity, transparency and patternability offered by ph-PSQs gives the exceptional possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Recently, we further developed optical sensors based on extended plasmons by using a patternable sol-gel hybrid film to fabricate a dielectric-metal-dielectric (DMD) sinusoidal grating capable of coupling light and generating surface plasmon polaritons [ 28 ]. We used aryl-bridged polysilsesquioxane films similar to those described earlier thanks to their ability to undergo patterning and to their distinctive ability to detect aromatic hydrocarbons.…”
Section: Sol-gel Nanomaterials For Optical Sensors Based On Extendmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we further developed optical sensors based on extended plasmons by using a patternable sol-gel hybrid film to fabricate a dielectric-metal-dielectric (DMD) sinusoidal grating capable of coupling light and generating surface plasmon polaritons [ 28 ]. We used aryl-bridged polysilsesquioxane films similar to those described earlier thanks to their ability to undergo patterning and to their distinctive ability to detect aromatic hydrocarbons.…”
Section: Sol-gel Nanomaterials For Optical Sensors Based On Extendmentioning
confidence: 99%
“…The glass prism can also be replaced by a diffraction grating: for a proper combination of the period of the grating, the angle and wavelength of the incident wave, a surface plasmon is generated [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A postdeposition bake was applied to promote solvent evaporation and reach a stable cross-linking degree. [22] TiO 2 -based anatase TiO 2 nanoparticles (NPs) were synthesized starting from a solution containing water, HCl and methanol with molar ratios H 2 O/TiOPr=12.25 and HCl/ TiOPr=1.72. Following a previously described receipt, 10.5 mmol of Ti(OPri) 4 (Titanium Isopropoxide) were added drop wise into the solution, that was stirred for 60 min at room temperature afterwards, then heated in an oil bath at 70°C and kept at this temperature for 4 h under reflux.…”
Section: Functional Resist Ph-psqmentioning
confidence: 99%
“…Therefore, reflectance spectra could only be acquired at an incidence angle of 70°, varying the incident light frequency. [22] In order to test the sensor response to a specific analyte, the following procedure was adopted. First, a suitable reference reflectance spectrum was recorded in dry N 2 environment.…”
Section: Sensing Measurementsmentioning
confidence: 99%
“…It is thus essential to find strategies to enhance the sensitivity of these sensors. It was demonstrated that a sensitivity enhancement can be achieved by working in "conical mounting", a configuration where the scattering plane is rotated of an azimuthal angle with respect to the grating wavevector [25][26][27][28]. It was also observed that the symmetry breaking, due to the azimuthal rotation, involves a fundamental role of the incident light polarization on SPP excitation [25,29].…”
Section: Introductionmentioning
confidence: 99%